Improving Students Activity and Students Mathematic Learning Outcomes by Using Scientific Learning Approach - Sholahudin Al Ayubi (Universitas Islam Jember, 2017)
The purpose of the research to describe the using of scientific learning approach for increasing the mathematical students activities and to describe the using of scientific learning approach for increasing the mathematicl students learning outcomes. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VII at MTs. Ma’arif NU Jenggawah. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: scientific, students activity, and learning outcomes